Normal and threshold values of radiographic parameters for knee osteoarthritis using a computer-assisted measuring system (KOACAD): the ROAD study - Oka, Hiroyuki; Muraki, Shigeyuki; Akune, Toru; Nakamura, Kozo; Kawaguchi, Hiroshi; Yoshimura, Noriko (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2010)
Although radiographic severity of the knee is commonly determined by the Kellgren-Lawrence (KL) grading scale, it does not separately assess joint space narrowing or osteophyte formation. The present study aimed to establish normal and threshold values of radiographic parameters for knee osteoarthritis (OA) using the knee osteoarthritis computer-aided diagnosis (KOACAD) measuring system on a large-scale population-based cohort of the Research on Osteoarthritis/Osteoporosis Against Disability (ROAD) population. From a total of 3040 participants in the ROAD study, standing anteroposterior radiographs of the knee were obtained from 2975 subjects (1041 men, 1934 women) in the ROAD cohort, and 5950 knees were evaluated using the KOACAD system to obtain the medial and lateral minimum joint space width (mJSW), medial and lateral joint space area (JSA), osteophyte area (OPA), and femorotibial angle (FTA). These indices were compared with the KL scores, and cutoff values for radiographic knee OA were determined by receiver operating characteristic (ROC) curve analysis. The mean KOACAD parameters for KL = 0 were as follows: medial mJSW 3.70mm; lateral mJSW 4.77mm, medial JSA 125.0mm2, lateral JSA 140.0mm2, OPA 0, and FTA 176.1° in men; for women they were medial mJSW 3.26mm, lateral mJSW 4.22mm, medial JSA 100.9mm2, lateral JSA 111.0mm2, OPA 0, and FTA 174.9°. Threshold values for KL ≥ 2 provided by ROC curve analysis with area under the curve (AUC) > 0.7 were medial mJSW 2.8mm and medial JSA 107.3mm2 in men and medial mJSW 2.7mm in women. Those for KL ≥ 3 were medial mJSW 2.1mm, medial JSA 81.1mm2, OPA 2.4mm2, and FTA 179.6° in men; and medial mJSW 2.1mm, medial JSA 66.6mm2, OPA 2.5mm2, and FTA 178.1° in women. We then determined the cutoff values for medial knee OA and lateral knee OA. The present study established normal and threshold values of parameters for knee OA using an automated computer-assisted program on plain radiographs.